Teorie (mexicko‑americké) hranice: Mestické vědomí Glorie Anzaldúy - Tereza Jiroutová Kynčlová (Gender a Výzkum, 2012)
Border theory, an interdisciplinary approach to the analysis of cultures located (especially) on the U.S.-Mexican border, was to a great extent initiated by the publication of Gloria Anzaldúa’s multigenre masterpiece Borderlands/La Frontera – The New Mestiza (1987), which in terms of postcolonial studies resists the canon of American literature and puts forth an indigenous, geographically and culturally situated theoretical concept of Mestiza consciousness which aims to defy Western dualistic thinking. The article, rooted in postcolonial perspectives and literary studies, looks at historical concepts of the American border, investigates the metaphorization of the US-Mexican borderlands in Anzaldúa’s work and explains her notion of Mestiza consciousness.